Conversor CC-CC Bidirecional Intercalado com Isolamento Monofásico de Alta Frequência para Aplicações no Setor Automobilístico e Energias Renováveis - Cavalcante, Kassio Derek Nogueira (2023)
Vehicles that use electricity as a way of obtaining energy to generate movement have emerged as protagonists to assume this role in the near future. In this context, energy converters are of vital importance for the consolidation of these vehicles and their acceptance by the population, thus contributing to the reduction of pollutant emissions. Thus, the present work presents a topology proposal for isolated bidirectional DC-DC converters with different pulse width modulations (PWM), one for each direction of power flow, with possible applications in electric vehicle charging centers as a stage DCDC, interaction with the electrical grid (V2G), charger onboard the electric and hybrid vehicle with regenerative braking, in addition to possible application in the production of green hydrogen, among others. This study presents the gains in continuous (MCC), discontinuous (MCD) and critical (MCCr) conduction modes in both directions of energy flow, qualitative and quantitative analysis in steady state, in addition to the voltage and current efforts in each converter element. The topology prototype was built for a nominal power of 2.5 kW in both directions of operation and considering the MCC converter. The results collected support the theoretical study and simulations carried out, highlighting as main points the four-fold increase in the ripple frequency (100 kHz) of voltage and current over passive filter elements in relation to the switching frequency (25 kHz), a fact which provides a reduction in the mass and volume of these filters, the possibility of operation as a step-down converter (buck) operating from 380Vdc to 180 Vdc or a step-up converter (boost) operating from 180 Vdc to 380 Vdc and balancing the electrical current between the arms of the converter.